КОНЦЕПТУАЛЬНА МОДЕЛЬ МІКРОМЕРЕЖІ З РОЗПОДІЛЕНИМИ ЕНЕРГЕТИЧНИМИ РЕСУРСАМИ - Нерубацький, В.П.; Гордієнко, Д.А. (Інститут електродинаміки Національної академії наук України, 2023)
Mіcrоnеtwоrk configurations are considered regarding the form of electricity transmission and distribution. The structures of connected units of dіstrіbutеd еnеrgy rеsоurcеs under different operating modes are described, in which special attention is paid to the primary control elements of dіstrіbutеd еnеrgy rеsоurcеs units for the instantaneous balance of active and reactive power, as well as to dispatch control architectures for long-term energy management. The characteristics of static and dynamic load are studied, the simulation of which is carried out by building physical models of typical loads. The parameters of the system of instantaneous balances of active and reactive power in mіcrоnеtwоrks determined by instantaneous load tracking and load distribution between blocks of distributed energy resources are obtained. The circuit of resistive active filtering of blocks of distributed energy resources for active compensation of distorted loads is given. The presented method effectively suppresses harmonic voltage distortions at the output of blocks of dіstrіbutеd еnеrgy rеsоurcеs. Ref. 10, fig. 2.